Organotin(IV) complexes derived from hydrazone ligands: Synthesis, spectral analysis, antimicrobial and molecular docking studies. (30th September 2022) - Kumar, Naresh; Asija, Sonika; Deswal, Yogesh; Saroya, Sonia; Kumar, Ashwani; Devi, Jai
Abstract: The goal of this research work is to create a new class of diorganotin(IV) complexes with general formula R2 SnL 1-4, where R = CH3, C2 H5, C4 H9 & C6 H5, and L 1-4 are the Schiff base ligands derived from the condensation of indole-3-acetic acid hydrazide with salicylaldehyde derivatives in 1:1 molar ratio. Various spectral (FTIR, NMR and mass spectrometry) and physico-chemical (XRD, TGA) techniques were utilized to identify the structure of the prepared compounds. Spectroscopic evidence suggests that Schiff base ligands coordinate to the central tin atom in a tridentate manner with ONO as the donor site, thus forming a pentacoordinate environment around the metal ion. The serial dilution method was employed for carrying out the antimicrobial activity of the produced compounds against four bacterial strains and two fungal strains. The observed results of biocidal activity showed that compounds Ph2 SnL 3 (16 ) and Ph2 SnL 4 (20 ) were found to be most potent against the tested strains. Further, molecular docking studies for active compounds i.e., 16 and 20 were carried out in the active site of Escherichia coli 3-oxoacyl-[acyl-carrier-protein] synthase 2 (FabF). To check the drug-likeness, in silico studies of the synthesized compounds was carried out and it has been found that compounds can be used as orally active drugs. GRAPHICAL ABSTRACT: UF0001